RANCANGAN SISTIM MANAJEMEN KINERJA PADA PT X - Rachmi Endrasprihatin (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Bina Insani, 2014)
Performance Management System is believed become a strategic tool to conduct the organizational change. PT. X is a private company with a significant growth for more than the last ten years ago. Its Strategic Plan 2012 -2016 states that it would like to become the five star hospitality company in its industry. To achieve this objective, the company need to know its performance through its employees’ performance. The last two years before shows that its employee’ performance are mostly in an excellent result. But on the other hand, the management does not feel this way. In order to make this clear for management, they need to review their Performance System and redesign it. This research is qualitative research, which used an interview and document study to collect the data and information. The result is Performance Management System for PT X then is decided to redesign by referring to four phases of Performance Management System, which are Planning, Monitoring, Evaluating and Rewarding.